Mosquito Hemocytes Associate With Circulatory Structures That Support Intracardiac Retrograde Hemolymph Flow - Sigle, Leah T.; Hillyer, Julián F. (Frontiers in Physiology, 2018)
A powerful immune system protects mosquitoes from pathogens and influences their ability to transmit disease. The mosquito’s immune and circulatory systems are functionally integrated, whereby intense immune processes occur in areas of high hemolymph flow. The primary circulatory organ of mosquitoes is the dorsal vessel, which consists of a thoracic aorta and an abdominal heart. In adults of the African malaria mosquito, Anopheles gambiae, the heart periodically alternates contraction direction, resulting in intracardiac hemolymph flowing toward the head (anterograde) and toward the posterior of the abdomen (retrograde). During anterograde contractions, hemolymph enters the dorsal vessel through ostia located in abdominal segments 2-7, and exits through an excurrent opening located in the head. During retrograde contractions, hemolymph enters the dorsal vessel through ostia located at the thoraco-abdominal junction, and exits through posterior excurrent openings located in the eighth abdominal segment. The ostia in abdominal segments 2-7 – which function in anterograde intracardiac flow – are sites of intense immune activity, as a subset of hemocytes, called periostial hemocytes, respond to infection by aggregating, phagocytosing, and killing pathogens. Here, we assessed whether hemocytes are present and active at two sites important for retrograde intracardiac hemolymph flow: the thoraco-abdominal ostia and the posterior excurrent openings of the heart. We detected sessile hemocytes around both of these structures, and these hemocytes readily engage in phagocytosis. However, they are few in number and a bacterial infection does not induce the aggregation of additional hemocytes at these locations. Finally, we describe the process of hemocyte attachment and detachment to regions of the dorsal vessel involved in intracardiac retrograde flow.